Separator, secondary battery, and electric device
Patent Information
- Application Number
- CN202380056565.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-03-18
AI Technical Summary
Under high energy density design, long cycle, and high temperature conditions, the electrodes of secondary batteries are easily damaged, resulting in battery capacity attenuation, and the electrolyte components have different compatibility with the positive and negative electrodes, which limits the personalized design of the battery and increases the cost. cost.
An isolation membrane is used. The coating contains a covalent organic framework material. By regulating the volume average particle size of the material, the pore size of the internal pores and the thickness of the coating, only lithium ions are allowed to pass through, inhibiting the interaction between electrodes and reducing the number of electrodes. Destruction and capacity fading.
It effectively reduces electrode damage, improves the high-temperature capacity retention rate and long-cycle capacity retention rate of secondary batteries, reduces the cost of the battery, and optimizes the design of the electrolyte.
Smart Images

Figure 00000027_0000 
Figure 00000027_0001 
Figure 00000027_0002
Abstract
Description
Separator, secondary battery and electrical device Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an isolation membrane, a secondary battery, and an electrical device. Background Art
[0002] In recent years, as people's awareness of green travel and low-carbon living continues to strengthen, the market demand for secondary batteries has grown, and their applications have become increasingly broad. Complex market demands are driving the development of batteries towards higher energy density, longer cycle life, and greater environmental adaptability.
[0003] However, under conditions such as high energy density design, long cycle, and high temperature, the electrodes are often severely damaged, causing battery capacity decay.
[0004] Summary of the Invention
[0005] In view of the technical problems existing in the background technology, the present application provides an isolation membrane, a secondary battery and an electrical device, aiming to reduce damage to the electrodes and reduce battery capacity attenuation.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides an isolation film, comprising:
[0007] diaphragm substrate;
[0008] a coating layer located on at least one side of the membrane substrate, the coating layer comprising a covalent organic framework material;
[0009] The pore size of the internal pores of the covalent organic framework material is recorded as D, the volume average particle size Dv50 of the covalent organic framework material is recorded as d, and the total thickness of the coating is recorded as L. The pore size of the internal pores of the covalent organic framework material satisfies: 0.04nm≤D≤5nm, the volume average particle size Dv50 of the covalent organic framework material and the total thickness of the coating satisfy: 50≤L / d≤2000.
[0010] Compared with the prior art, this application has at least the following beneficial effects:
[0011] The isolation membrane of the present application is provided with a coating, and the coating contains a covalent organic framework material. By regulating the volume average particle size of the covalent organic framework material, the pore size of its internal pores and the total thickness of the coating, the isolation membrane can only allow lithium ions to pass through. If the volume average particle size of the covalent organic framework material is large, the total thickness of the coating can be increased to increase the tortuosity of the lithium ions and other substances in the positive electrode electrolyte and / or the negative electrode electrolyte through the gaps between the covalent organic framework material particles. If the volume average particle size of the covalent organic framework material is small, when the coating thickness is small, the tortuosity of the lithium ions and other substances through the gaps between the covalent organic framework material particles can still be large, and at the same time, when the coating thickness is small, its ion conductivity can be improved. When L / d is within the above range, lithium ions and other substances cannot pass through the coating via the tortuosity of the gaps between the covalent organic framework material particles. At the same time, when the pore size of the internal pores of the covalent organic framework material is within the above range, lithium ions can pass through the coating through the internal pores of the covalent organic framework material only after desolvation, while other components in the electrolyte cannot pass through the coating along with the lithium ions via this path, thereby suppressing the interaction between the positive and negative electrodes, thereby reducing damage to the electrodes and reducing battery capacity attenuation.
[0012] In any embodiment of the present application, the pore size of the internal pores of the covalent organic framework material, the volume average particle size Dv50 of the covalent organic framework material, and the total thickness of the coating satisfy the following requirements:
[0013] In any embodiment of the present application, the pore diameter of the internal pores of the covalent organic framework material satisfies: 0.04 nm ≤ D ≤ 2 nm.
[0014] In any embodiment of the present application, the volume average particle size Dv50 of the covalent organic framework material satisfies: 5nm≤d≤200nm; optionally 20nm≤d≤100nm.
[0015] In any embodiment of the present application, the total thickness of the coating satisfies: 2 μm≤L≤30 μm; optionally 5 μm≤L≤15 μm.
[0016] In any embodiment of the present application, the covalent organic framework material includes one or more of homopolymers and copolymers of M2 monomers, M3 monomers, M4 monomers and M6 monomers;
[0017] Among them, the M2 monomer includes 2 functional groups that can participate in the polymerization reaction, the M3 monomer includes 3 functional groups that can participate in the polymerization reaction, the M4 monomer includes 4 functional groups that can participate in the polymerization reaction, and the M6 monomer includes 6 functional groups that can participate in the polymerization reaction.
[0018] In any embodiment of the present application, the functional group capable of participating in the polymerization reaction includes one or more of a carboxyl group, a hydroxyl group, an aldehyde group, an amino group, a borate group, a hydrazine group, a cyano group, a carbonyl group and an anhydride group.
[0019] In any embodiment of the present application, the covalent organic framework material includes one or more of a copolymer of the M2 monomer and the M3 monomer and a copolymer of the M2 monomer and the M6 monomer.
[0020] In any embodiment of the present application, the connecting groups between the monomers polymerized to form the covalent organic framework material include One or more of boryloxy, -C=N-, triazine group, -C=NN=C-, -C=C-, -CO-NH-, -C=N-NH-CO- and imidazole group.
[0021] In any embodiment of the present application, the mass proportion of the covalent organic framework material in the coating is 80% to 96%.
[0022] In any embodiment of the present application, the coating further comprises a binder; optionally, the binder accounts for 4% to 20% by mass in the coating.
[0023] In any embodiment of the present application, the binder includes one or more homopolymers or copolymers of vinylidene fluoride, ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, acrylic acid, and acrylonitrile.
[0024] In any embodiment of the present application, the diaphragm substrate includes one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0025] A second aspect of the present application provides a secondary battery comprising the separator of the first aspect of the present application.
[0026] In any embodiment of the present application, the secondary battery further comprises: a positive electrode sheet, a negative electrode sheet, a positive electrode electrolyte and a negative electrode electrolyte;
[0027] The isolation membrane is located between the positive electrode sheet and the negative electrode sheet, the positive electrode electrolyte is located between the positive electrode sheet and the isolation membrane, and the negative electrode electrolyte is located between the negative electrode sheet and the isolation membrane; one or more of the solvents, lithium salts and additives contained in the positive electrode electrolyte and the negative electrode electrolyte are different.
[0028] In any embodiment of the present application, the solvent of the positive electrode electrolyte is different from the solvent of the negative electrode electrolyte;
[0029] Optionally, the solvent of the positive electrode electrolyte includes one or more of carbonate solvents, fluorocarbonate solvents, fluorocarboxylate solvents, sulfone solvents, fluorosulfone solvents, phosphate solvents, borate solvents and nitrile solvents;
[0030] Optionally, the solvent of the negative electrode electrolyte includes one or more of a carbonate solvent, a carboxylate solvent, an ether solvent, a fluorinated carboxylate solvent, and a fluorinated carbonate solvent.
[0031] In any embodiment of the present application, the fluorocarbonate solvent includes one or more of methyl trifluoroethyl carbonate, bis(trifluoromethyl) carbonate, bis(trifluoroethyl) carbonate, 4-trifluoromethyl ethylene carbonate, bisfluoroethylene carbonate, trifluoromethyl trifluoroethyl carbonate, trifluoropropyl carbonate and 2,2-difluoroethyl methyl carbonate;
[0032] The fluorocarboxylate solvent includes one or more of trifluoroethyl 3,3,3-trifluoroacetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate and 2,2,2-trifluoroethyl acetate;
[0033] The sulfone solvent includes one or more of sulfolane, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, diethyl sulfoxide and methyl ethyl sulfoxide;
[0034] The fluorinated sulfone solvent includes one or more of methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, propyl trifluoromethyl sulfone, methyl trifluoroethyl sulfone, methyl trifluoropropyl sulfone, 1,1,2,2-tetrafluoropropyl methyl sulfone, trifluoromethyl isopropyl sulfone and methyl hexafluoroisopropyl sulfone;
[0035] The phosphate ester solvent includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, isopropyl phosphate, tris(hexafluoroisopropyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate;
[0036] The borate ester solvent includes one or more of trimethyl borate, triethyl borate, tris(hexafluoroisopropyl) borate and tris(2,2,2-trifluoroethyl) borate;
[0037] The nitrile solvent includes one or more of acetonitrile, succinonitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyano-2-butene, 1,3,6-hexanetrinitrile, ethylene glycol dipropionitrile ether and 1,2,3-tricyanoethoxy;
[0038] The carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate;
[0039] The carboxylate solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate;
[0040] The ether solvent includes one or more of 1,2-dimethoxyethane, tetraethanol dimethyl ether, γ-butyrolactone and tetrahydrofuran.
[0041] In any embodiment of the present application, the lithium salt of the positive electrode electrolyte is different from the lithium salt of the negative electrode electrolyte;
[0042] Optionally, the lithium salt of the positive electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate);
[0043] Optionally, the lithium salt of the negative electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate).
[0044] In any embodiment of the present application, the positive electrode plate includes:
[0045] positive electrode current collector;
[0046] a positive electrode active material layer, located on at least one side of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material;
[0047] Optionally, the positive electrode active material includes lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and one or more compounds obtained by adding other transition metal elements or non-transition metal elements to the above lithium-containing compounds.
[0048] In any embodiment of the present application, the negative electrode plate includes:
[0049] negative electrode current collector;
[0050] a negative electrode active material layer, located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material;
[0051] Optionally, the negative electrode active material includes one or more of carbon-based materials, silicon-based materials, lithium metal, lithium-carbon composite materials and lithium titanate;
[0052] Further optionally, the carbon-based material includes one or more of graphite, soft carbon, hard carbon, mesocarbon microbeads, carbon fibers and carbon nanotubes;
[0053] Further optionally, the silicon-based material includes one or more of elemental silicon, silicon oxides, and silicon-carbon composites.
[0054] A third aspect of the present application provides an electrical device comprising the secondary battery of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0056] FIG1 is a schematic diagram of the TC-1 structure provided in one embodiment of the present application.
[0057] FIG2 is a schematic diagram of the TC-2 structure provided in an embodiment of the present application.
[0058] FIG3 is a schematic diagram of the TC-3 structure provided in one embodiment of the present application.
[0059] FIG4 is a schematic diagram of the TC-4 structure provided in one embodiment of the present application.
[0060] FIG5 is a schematic diagram of the TC-5 structure provided in one embodiment of the present application.
[0061] FIG6 is a schematic diagram of the TC-6 structure provided in an embodiment of the present application.
[0062] FIG7 is a schematic diagram of the TC-7 structure provided in one embodiment of the present application.
[0063] FIG8 is a schematic diagram of the TC-8 structure provided in one embodiment of the present application.
[0064] FIG9 is an X-ray diffraction spectrum of TC-1.
[0065] FIG10 is the infrared spectrum of TC-1.
[0066] FIG11 is a gas adsorption diagram of TC-1.
[0067] FIG. 12 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0068] FIG. 13 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 12 .
[0069] FIG. 14 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0070] Description of reference numerals: 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate; 2 power-consuming device. DETAILED DESCRIPTION
[0071] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0072] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.
[0073] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0074] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0075] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0076] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0077] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0078] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” include the number itself, and “several” in “one or several” means two or more.
[0079] In the description herein, unless otherwise stated, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). Unless otherwise stated, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0080] Currently, secondary batteries often suffer severe damage to their electrodes and battery capacity decay under conditions such as high energy density, long cycles, and high temperatures. The technical staff of this application analyzed and found that under these conditions, the reactions between the positive electrode, negative electrode, and electrolyte of the battery continue to intensify, producing complex and diverse byproducts. These byproducts propagate through the electrolyte, diffuse between the positive and negative electrodes, and further react on the other side, causing damage to the electrodes and battery capacity decay.
[0081] In addition, some electrolyte components often have different compatibilities with the positive and negative electrodes. They may have a positive effect on one side and a side effect on the other. In order to balance the two, the electrolyte design has gradually become more complex, which limits the personalized design of the battery and also increases the cost of the battery. In order to take into account both the positive and negative electrodes, the solvents and lithium salts that can be selected for the electrolyte are very limited, and the advantages of each electrolyte component cannot be brought into play.
[0082] The isolation membrane provided in the present application includes: a membrane substrate and a coating located on at least one side of the membrane substrate, the coating including a covalent organic framework material; wherein the pore size of the internal pores of the covalent organic framework material is denoted as D, the volume average particle size Dv50 of the covalent organic framework material is denoted as d, and the total thickness of the coating is denoted as L, then the pore size of the internal pores of the covalent organic framework material satisfies: 0.04nm≤D≤5nm, the volume average particle size Dv50 of the covalent organic framework material and the total thickness of the coating satisfy: 50≤L / d≤2000.
[0083] It should be noted that covalent organic framework materials (hereinafter referred to as COF materials) are a type of crystalline organic porous materials that connect functional units in the form of covalent bonds into highly ordered two-dimensional stacked structures or specific three-dimensional topological structures based on reversible chemical reactions.
[0084] The separator of the present application may be coated on only one side of the separator substrate, or on both sides. The coating may be applied as needed. If the coating is applied on only one side of the separator substrate, the total coating thickness refers to the thickness of the coating on that single side. If the coating is applied on both sides of the separator substrate, the total coating thickness refers to the sum of the thicknesses of the coatings on both sides.
[0085] For example, if the volume average particle size (Dv50) of the COF material is large, the corresponding coating thickness needs to be thicker. The coating can be applied on one side of the separator substrate or on both sides of the separator substrate. Applying the coating on both sides of the separator substrate is preferred to reduce the thickness of a single coating layer and improve the processability of the separator. Furthermore, it is preferred that the coating thickness on both sides be the same. If the volume average particle size (Dv50) of the COF material is small, the coating can be applied only on one side of the separator substrate. A thin coating thickness can achieve a barrier effect, meaning a thin coating on a single side can achieve a barrier effect, which helps improve the coating's ion conductivity.
[0086] It should be noted that the coating may include only one COF material, or may include two or more COF materials at the same time.
[0087] It can be understood that the above-mentioned isolation film is provided with a coating layer containing COF material.
[0088] The volume average particle size Dv50 of the material, the pore size of its internal pores, and the total thickness of the coating can make the separator only allow lithium ions to pass through. If the volume average particle size Dv50 of the COF material is large, the total thickness of the coating can be increased to increase the tortuosity of the lithium ions and other substances in the positive electrode electrolyte and / or negative electrode electrolyte passing through the gaps between the COF material particles, thereby inhibiting the transmission of lithium ions and other substances through the gaps between the COF material particles. If the volume average particle size Dv50 of the COF material is small, the gaps between the particles are smaller, and the resistance to the transmission of lithium ions and other substances in the electrolyte through the gaps between the COF material particles is large. A smaller coating thickness can play a barrier role, and a smaller coating thickness can also improve its ion conductivity. When L / d is within the above range, lithium ions and other substances cannot pass through the coating via the tortuosity of the gaps between the COF material particles; at the same time, when the pore size of the internal pores of the COF material is within the above range, lithium ions can pass through the coating through the internal pores of the COF material only after desolvation, while other components in the electrolyte cannot pass through the coating along with the lithium ions via this path, thereby suppressing the interaction between the positive and negative electrodes, reducing electrode damage and reducing battery capacity attenuation; and reducing the negative electrode side reaction caused by the diffusion of components in the electrolyte on the positive electrode side to the negative electrode side, thereby reducing the gas production caused by the negative electrode side reaction, and the volume change of the battery cell is correspondingly reduced.
[0089] The pore size of the internal pores of the COF material mentioned in this application satisfies the following: 0.04nm≤D≤5nm; for example, it can be 0.04nm≤D≤4.5nm, 0.04nm≤D≤4nm, 0.04nm≤D≤3.5nm, 0.04nm≤D≤3nm, 0.04nm≤D≤2.5nm, 0.04nm≤D≤2nm, 0.04nm≤D≤1.5nm, 0.04nm≤D≤1nm, 0.04nm≤D≤0.5nm or 0.04nm≤D≤0.1nm, etc. When the pore size of the internal pores of the COF material is within the above range, the pore size of the internal pores of the COF material is close to the solvation diameter of lithium ions, and only desolvated lithium ions are allowed to pass through the diaphragm through the internal pores of the COF material, thereby realizing solid-phase transport of lithium ions, preventing other substances in the electrolyte other than lithium ions from passing through the diaphragm, and inhibiting the interaction between the positive and negative electrodes. As an example, the pore size of the internal pores of the COF material may be 0.04 nm, 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, or 5 nm, etc.
[0090] Further preferably, the pore size of the internal pores of the COF material satisfies: 0.04 nm ≤ D ≤ 2 nm; this can promote more complete desolvation of lithium ions and better prevent other substances in the electrolyte from passing through the separator.
[0091] It should be noted that other substances in the electrolyte include complex and diverse by-products produced when the positive electrode, negative electrode, electrolyte, etc. of the secondary battery react.
[0092] In the present application, the volume average particle size Dv50 of the COF material and the total thickness of the coating satisfy: 50≤L / d≤2000; for example, it can be 100≤L / d≤2000, 200≤L / d≤1900, 300≤L / d≤1800, 400≤L / d≤1700, 500≤L / d≤1600, 600≤L / d≤1500, 700≤L / d≤1400, 800≤L / d≤1300, 900≤L / d≤1200 or 1000≤L / d≤1100, etc. In related art, in separators with coatings, the ratio of the coating thickness to the volume average particle size (Dv50) of the coating material is generally 10-30. In the present application, when the ratio of the total coating thickness to the volume average particle size (Dv50) of the COF material is within this range, it is significantly more difficult for lithium ions and other substances in the electrolyte to pass through the coating through the gaps between the COF material particles, thereby effectively preventing lithium ions and other substances in the electrolyte from passing through the gaps between the COF material particles. As an example, the ratio of the coating thickness to the volume average particle size (Dv50) of the COF material can be 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, or 2000, etc.
[0093] The Dv50 of the COF material mentioned above refers to the particle size corresponding to 50% in the volume distribution. As an example, it can be tested using the following method: using a Microtrac MRB S3500 series laser particle size analyzer; taking the separator and placing it in NMP or water to soak for 24 hours, and then ultrasonicating it for 2 hours to remove the separator coating; filtering the detached material powder and re-immersing it in a new NMP solvent or water for 2 hours, and then ultrasonicating it for 2 hours to fully disperse the particles. Repeat the ultrasonic cleaning process for more than 3 times to finally obtain the coating powder material and place it in a vacuum drying oven at 80°C for 24 hours. The resulting coating material is placed in deionized water and ultrasonicated for 5 minutes to ensure that the sample is completely dispersed. The dispersion is then placed in a sample tank and tested to obtain the volume average particle size Dv50 of the COF material. Optionally, the mass of the coating can be 0.05g-2g, and the volume of deionized water can be 10mL-20mL.
[0094] As an example, the pore diameter of the internal pores of the above-mentioned COF material can be measured by the following method: Take the separator and soak it in NMP or water for 24 hours. After soaking, ultrasonic for 2 hours to make the separator coating fall off; filter the fallen material powder, and put it back into a new NMP solvent or water and soak for 2 hours, and then ultrasonic for 2 hours to fully disperse the particles. Repeat the cleaning and ultrasonic process more than 3 times. Finally, obtain the coated powder material and put it into a vacuum drying oven at 80 °C for 24 hours. Use a gas adsorption instrument of model Quantachrome (ASiQMVH002 5) to measure the adsorption amount of N2 by the prepared COF material under standard atmospheric pressure (101 kPa). The purity of the gas used for testing is 99.999%; Add 100 mg of the coated powder material to a quartz sample tube and degas it under vacuum at 120 °C for 6 hours on the pretreatment station of a rapid specific surface area analyzer. Use a gas adsorption instrument to conduct a gas adsorption experiment on the COF material. According to the obtained nitrogen adsorption curve, use the non-local density functional theory model (NLDFT) to calculate the BET specific surface area of the COF material for the adsorption data in the low-pressure range (0.0255 < P / P0 < 0.2), and calculate the pore volume at P / P0 = 0.99; The pore size distribution (PSD) is obtained by calculation using the non-local density function theory (NLDFT).
[0095] As an example, the thickness of the above-mentioned coating can be measured by the following method: First, calibrate the micrometer, then place the separator between the two anvils, gently rotate the sleeve until a sound appears, and record the separator thickness by reading; Remove the separator and remove the coating to obtain the separator substrate, repeat the above measurement process, and measure the thickness of the separator substrate; Subtract the thickness of the separator substrate from the thickness of the separator to obtain the thickness of the coating.
[0096] The inventors of the present application have found through in-depth research that when the separator of the present application meets the above design conditions, if it also optionally meets one or more of the following conditions, the high-temperature capacity retention rate and long-cycle capacity retention rate of the secondary battery can be further improved.
[0097] In some of these embodiments, the pore diameter of the internal pores of the COF material, the volume average particle diameter Dv50 of the COF material, and the total thickness of the coating satisfy:
[0098] Generally, electrolyte components travel through the separator in two ways: one is diffusion through the pores between the coating material particles, which is liquid-phase transmission; the other is transmission through the pores within the coating material particles, which is solid-phase transmission. Liquid-phase transmission has low resistance but high tortuosity and a long transmission path, while solid-phase transmission has the opposite effect. The lithium ion transmission path depends on four factors: the internal pores of the coating material particles, the pores between the coating material particles, the volume average particle size (Dv50) of the coating material particles, and the coating thickness. The pores between the coating material particles are related to the volume average particle size (Dv50) of the coating material particles, while the coating thickness and the volume average particle size (Dv50) of the coating material particles determine the tortuosity of the liquid-phase transmission.
[0099] This application constructs the above relationship by regulating the volume average particle size Dv50 of the COF material, the pore size of the internal pores and the total thickness of the coating. When the three satisfy this relationship, the isolation membrane can have the characteristics of solid-phase transmission.
[0100] First, when the coating thickness is equal to the volume average particle size Dv50 of the COF material, that is, L = d, the tortuosity of lithium ion transmission through the liquid phase is consistent with that of solid phase transmission. As long as the pores between the COF material particles are smaller than the pores inside the COF material, that is, Lithium ions have the advantage of being transported through the internal pores of COF materials. Further deformation of the formula yields
[0101] Secondly, when the total thickness of the coating is greater than the volume average particle size Dv50 of the COF material, that is, L>d, with each additional layer of COF material particles accumulated, the tortuosity of lithium ion transmission through the liquid phase becomes greater, and the tortuosity is related to the number of accumulated layers. When the tortuosity reaches a certain value, lithium ions tend to be transported in the solid phase with less resistance. Therefore, when L>d, due to the large tortuosity of liquid phase transmission, even if the pores between COF material particles are larger than the pores inside the COF material, lithium ions tend to be transported in the solid phase. At this time, the relationship can be expressed as Introducing correction items Further integration yields the relationship between the pore size of the COF material, the volume average particle size Dv50 of the COF material, and the total thickness of the coating: Where 1.42 is a correction constant representing the relationship between tortuosity and the volume average particle size Dv50 of COF material, which is obtained by experiment.
[0102] From the above analysis, it can be seen that the pore size of the internal pores of the COF material, the volume average particle size Dv50 of the COF material and the total thickness of the coating meet the following requirements: When the electrolyte is in a liquid phase, the lithium ions and other substances in the electrolyte cannot be transported in the liquid phase, and only the desolvated lithium ions can be transported in the solid phase through the isolation membrane. The isolation membrane can fully suppress the interaction between the positive and negative electrodes while maximizing the promotion of lithium ion transmission.
[0103] In some embodiments, the volume average particle size Dv50 of the covalent organic framework material satisfies: 5nm≤d≤200nm; for example, it can be 10nm≤d≤200nm, 20nm≤d≤190nm, 30nm≤d≤180nm, 40nm≤d≤170nm, 50nm≤d≤160nm, 60nm≤d≤150nm, 70nm≤d≤140nm, 80nm≤d≤130nm or 90nm≤d≤120nm, etc. The smaller the volume average particle size (Dv50) of the COF material, the smaller the gaps between the COF material particles, the denser the coating, and the greater the possibility of lithium ion transmission through the pores within the COF material particles. However, if the volume average particle size (Dv50) of the COF material is too small, more COF material particles are packed into the same volume, which increases the amount of binder used and the bonding requirements, and also worsens the processability and mechanical properties of the separator. When the volume average particle size (Dv50) of the COF material is within the above range, the density of the separator is improved while also improving the processability of the separator. As an example, the volume average particle size (Dv50) of the COF material can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, or 200 nm, etc. Optionally, the volume average particle size Dv50 of the covalent organic framework material satisfies: 20 nm ≤ d ≤ 100 nm.
[0104] In some embodiments, the total thickness of the coating satisfies the following conditions: 2μm≤L≤30μm; for example, it can be 3μm≤L≤28μm, 4μm≤L≤25μm, 5μm≤L≤23μm, 7μm≤L≤20μm, 10μm≤L≤17μm, or 12μm≤L≤15μm. When the total thickness of the coating is within the above range, the isolation membrane has excellent ion conductivity and a good barrier effect. As an example, the total thickness of the coating can be 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 17μm, 20μm, 23μm, 25μm, 28μm, or 30μm. Optionally, the total thickness of the coating satisfies the following conditions: 5μm≤L≤15μm.
[0105] In some embodiments, the covalent organic framework material includes one or more homopolymers and copolymers of M2 monomers, M3 monomers, M4 monomers and M6 monomers; wherein, the M2 monomer includes 2 functional groups that can participate in polymerization reactions, the M3 monomer includes 3 functional groups that can participate in polymerization reactions, the M4 monomer includes 4 functional groups that can participate in polymerization reactions, and the M6 monomer includes 6 functional groups that can participate in polymerization reactions.
[0106] It should be noted that the above-mentioned "homopolymer" refers to a polymer formed from only one of the above-mentioned monomers. The above-mentioned "copolymer" includes polymers formed from two of the above-mentioned monomers, polymers formed from three of the above-mentioned monomers, and polymers formed from all of the above-mentioned monomers.
[0107] It can be understood that the type of monomers that form the COF material and the number of functional groups possessed by the monomers determine the configuration of the COF material and also determine the pore size of the internal pores of the COF material; the larger the pore size of the internal pores of the COF material, the more conducive it is to lithium ion transmission, and the smaller the pore size of the internal pores of the COF material, the better the barrier effect of the isolation membrane.
[0108] Optionally, the covalent organic framework material includes one or more of a copolymer of an M2 monomer and an M3 monomer, and a copolymer of an M2 monomer and an M6 monomer. M2 and M3 monomers can be synthesized from a wide variety of raw materials. The copolymer of an M2 monomer and an M6 monomer has small internal pores and excellent barrier properties.
[0109] In some embodiments, the functional groups that can participate in the polymerization reaction include one or more of carboxyl groups, hydroxyl groups, aldehyde groups, amino groups, borate groups, hydrazine groups, cyano groups, carbonyl groups, and anhydride groups.
[0110] In some embodiments, the linking groups between monomers polymerized to form a covalent organic framework material include One or more of boryloxy, -C=N-, triazine group, -C=NN=C-, -C=C-, -CO-NH-, -C=N-NH-CO- and imidazole group.
[0111] The linking group mentioned above refers to the linking group between two adjacent monomer units in the covalent organic framework material.
[0112] It should be noted that the structural formula of the above-mentioned cyclic boryl group is The structural formula of the triazine group mentioned above is The structural formula of the above-mentioned imidazole group is The structural formula of the -CO-NH- group mentioned above is The structural formula of the -C=N-NH-CO- group mentioned above is
[0113] As an example, the monomers and the connecting groups between the monomers that are polymerized to form the COF material mentioned above can be determined by the following method: soak the isolation membrane in NMP or water for 24 hours, and then ultrasonicate for 2 hours to remove the membrane coating; filter the detached material powder and re-immerse it in new NMP solvent or water for 2 hours, and then ultrasonicate for 2 hours to fully disperse the particles. Repeat the cleaning and ultrasonication process for more than 3 times to finally obtain the coating powder material and dry it in a vacuum drying oven at 80°C for 24 hours. The X-ray diffraction spectrum is measured by an X-ray powder diffractometer, and the Fourier infrared spectrum and nuclear magnetic resonance spectrum are measured by an infrared spectrometer and a nuclear magnetic resonance spectrometer. The X-ray diffraction spectrum, Fourier infrared spectrum and nuclear magnetic resonance spectrum of the isolation membrane are combined to determine the structure of the COF material contained in the isolation membrane, and then determine the type of monomers that form the COF material and the connecting groups between the monomers. Among them, the X-ray powder diffractometer can be a Science Ultima IV X-ray powder diffractometer, and the infrared spectrometer can be a Bruker ALPHA with a wavelength range of 400 cm -1 ~4000cm -1 The infrared spectrometer and the nuclear magnetic resonance spectrometer can be a Bruker AV III 400 nuclear magnetic resonance spectrometer.
[0114] It should be noted that COF materials with different linking groups often exhibit different properties; for example, COF materials formed by -C=N-, triazine groups or -C=NN=C- are more stable in air and aqueous solutions and are more suitable for use in systems sensitive to air and water. The monomer side chains of COF materials connected by -C=N-NH-CO- groups are easier to modify, and the coating is easier to functionalize. Functionalization design can further promote lithium ion desolvation and improve the ion conductivity of the isolation membrane. Although COF materials connected by imidazole groups are more difficult to synthesize, they have the best stability and are beneficial for the application of secondary batteries under extreme conditions.
[0115] In some embodiments, the mass proportion of the covalent organic framework material in the coating is 80% to 96%; for example, it can be 82% to 96%, 84% to 96%, 86% to 96%, 88% to 96%, 91% to 96% or 93% to 96%, etc. When the mass proportion of the COF material in the coating is within the above range, the COF material particles are closely stacked and contacted, and have good ion conductivity. As an example, the mass proportion of the COF material in the coating can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% or 96%, etc. Optionally, the mass proportion of the covalent organic framework material in the coating is 90% to 96%.
[0116] As an example, the mass percentage of the COF material mentioned above in the coating can be determined using the following method: Analyze the membrane components using a thermogravimetric-differential scanning calorimeter: 15-25 mg of the membrane is placed in an alumina crucible with nitrogen as the shielding gas. After preheating at 25°C for 30 minutes, the temperature is raised to 600°C at a rate of 2°C / 10 minutes. The content of each component is determined based on the change in weight and heat. A Mettler TGA / DSC2 1600LF simultaneous thermal analyzer can be used.
[0117] In some embodiments, the coating further comprises a binder.
[0118] In some embodiments, the mass proportion of the binder in the coating is 4% to 20%; for example, it can be 4% to 19%, 4% to 17%, 4% to 15%, 4% to 13%, 4% to 11%, 4% to 9%, 4% to 7% or 4% to 5%, etc. When the mass proportion of the binder in the coating is within the above range, the coating has good adhesion and mechanical properties. As an example, the mass proportion of the binder in the coating can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc. Optionally, the mass proportion of the binder in the coating is 4% to 10%.
[0119] As an example, the mass percentage of the aforementioned binder in the coating can be determined using the following method: Analyze the membrane components using a thermogravimetric-differential scanning calorimeter: 15-25 mg of the membrane is placed in an alumina crucible with nitrogen as the shielding gas. After preheating at 25°C for 30 minutes, the temperature is raised to 600°C at a rate of 2°C / 10 minutes. The content of each component is determined based on the change in weight and heat. A Mettler TGA / DSC2 1600LF simultaneous thermal analyzer can be used.
[0120] In some embodiments, the binder comprises one or more of homopolymers or copolymers of vinylidene fluoride, ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, acrylic acid, and acrylonitrile. Alternatively, the binder comprises one or more of polyvinylidene fluoride, polyacrylic acid, polyvinyl alcohol, polyurethane, polyamide, and polyacrylonitrile.
[0121] It should be noted that the “copolymers” mentioned above include copolymers formed by two monomers, three monomers, four monomers, five monomers, six monomers, seven monomers, eight monomers and nine monomers among the above-mentioned vinylidene fluoride, ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, acrylic acid and acrylonitrile.
[0122] In some embodiments, the material of the separator substrate can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polyamide, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0123] In some embodiments, the isolation film has a thickness of 6-40 μm, and optionally 8-20 μm.
[0124] The present application also provides a method for preparing an isolation membrane, comprising the following steps:
[0125] Mixing all raw materials with solvent to prepare coating slurry;
[0126] The coating slurry is coated on the separator substrate to prepare the separator.
[0127] In some embodiments, the solvent is N-methylpyrrolidone.
[0128] As an example, the preparation method of the isolation membrane is: mixing the COF material and the binder, then adding a solvent to stir and disperse to form a coating slurry; coating the coating slurry on the isolation membrane substrate, and after coating, drying, cold pressing, and cutting to prepare the isolation membrane.
[0129] secondary batteries
[0130] The present application also provides a secondary battery comprising the aforementioned separator, thereby significantly improving the high-temperature capacity retention rate and long-cycle capacity retention rate of the resulting secondary battery.
[0131] The secondary battery, battery module, battery pack, and electric device of the present application are described below with reference to the accompanying drawings as appropriate.
[0132] In some embodiments, the secondary battery further comprises: a positive electrode sheet, a negative electrode sheet, a positive electrode electrolyte, and a negative electrode electrolyte;
[0133] The separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode electrolyte is located between the positive electrode sheet and the separator, and the negative electrode electrolyte is located between the negative electrode sheet and the separator; one or more of the solvents, lithium salts and additives contained in the positive electrode electrolyte and the negative electrode electrolyte are different.
[0134] It should be noted that, in some possible embodiments, when preparing a secondary battery, the positive electrode sheet and the negative electrode sheet can be stacked close to the isolation membrane, and then the three can be placed in an aluminum-plastic bag with the same length and width as the isolation membrane. Since the isolation membrane and the aluminum-plastic bag are the same length and width, the other three sides except the opening of the aluminum-plastic bag can be heat-sealed together with the isolation membrane. The isolation membrane and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber, and then the positive electrode electrolyte and the negative electrode electrolyte are respectively injected into the positive electrode chamber and the negative electrode chamber from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell, and the battery cell is placed in a shell. For example, the shell can be a steel shell to obtain a secondary battery.
[0135] As a possible implementation method, when preparing a secondary battery, the positive electrode sheet, the negative electrode sheet and the separator can be wound and then placed in an aluminum-plastic bag. The lower end of the aluminum-plastic bag is heat-sealed together with the separator. The separator and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber. The positive electrode electrolyte and the negative electrode electrolyte are then injected into the positive electrode chamber and the negative electrode chamber respectively from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell, and the battery cell is placed in a shell, for example, the shell can be a steel shell, to obtain a secondary battery.
[0136] It should be noted that in conventional electrolytes, the compatibility of solvents, lithium salts, and additives with the positive and negative electrodes often differ, so they are usually combined to protect both. In this application, because the separator can inhibit the exchange of positive and negative electrolytes, the electrolytes can be designed based on the characteristics of the positive and negative electrodes, without considering compatibility with the other side. This can further amplify the advantages of different electrolytes, improve the performance of the battery cell, and push the limits of electrolyte design.
[0137] In some embodiments, the solvent of the positive electrode electrolyte is different from the solvent of the negative electrode electrolyte.
[0138] It should be noted that when the types of solvents used in the positive electrode electrolyte and the negative electrode electrolyte are completely different, this falls under the category of having different solvents for the positive electrode electrolyte and the negative electrode electrolyte. For example, if the positive electrode electrolyte uses solvent A and the negative electrode electrolyte uses solvent B, then the solvents for the positive electrode electrolyte and the negative electrode electrolyte are different.
[0139] When both the positive and negative electrolytes utilize a mixture of multiple solvents, and the solvents used in the positive and negative electrolytes are the same, but the volume or mass ratios of the different solvents differ, this also falls under the category of having different solvents for the positive and negative electrolytes. For example, if the solvent used in the positive electrolyte is a mixture of A and B in a volume ratio of 5:5, and the solvent used in the negative electrolyte is a mixture of A and B in a volume ratio of 3:7, then the solvents for the positive and negative electrolytes are different.
[0140] When the positive and negative electrolytes use some of the same solvents, this also falls under the category of having different solvents for the positive and negative electrolytes. For example, if the positive electrolyte uses solvent A and the negative electrolyte uses a mixture of A and B, then the solvents for the positive and negative electrolytes are different. If the positive electrolyte uses a mixture of A and C, and the negative electrolyte uses a mixture of A and B, then the solvents for the positive and negative electrolytes are also different.
[0141] Understandably, using an oxidation-resistant solvent system for the positive electrolyte can significantly reduce electrolyte oxidation and improve battery cell performance. Using a solvent system that is compatible with the negative electrode and has a low viscosity for the negative electrolyte can significantly improve the negative electrode interface stability and increase the lithium ion transfer rate at the negative electrode.
[0142] Optionally, the solvent of the positive electrode electrolyte includes one or more of carbonate solvents, fluorinated carbonate solvents, fluorinated carboxylate solvents, sulfone solvents, fluorinated sulfone solvents, phosphate solvents, borate solvents and nitrile solvents.
[0143] Optionally, the solvent of the negative electrode electrolyte includes one or more of a carbonate solvent, a carboxylate solvent, an ether solvent, a fluorinated carboxylate solvent, and a fluorinated carbonate solvent.
[0144] In some embodiments, the fluorocarbonate solvents include one or more of methyl trifluoroethyl carbonate, bis(trifluoromethyl) carbonate, bis(trifluoroethyl) carbonate, 4-trifluoromethyl ethylene carbonate, bisfluoroethylene carbonate, trifluoromethyl trifluoroethyl carbonate, trifluoropropyl carbonate, and 2,2-difluoroethyl methyl carbonate; the fluorocarboxylate solvents include one or more of 3,3,3-trifluoroethyl trifluoroacetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate, and 2,2,2-difluoroethyl acetate. One or more of trifluoroethyl esters; sulfone solvents include one or more of sulfolane, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, diethyl sulfoxide and methyl ethyl sulfoxide; fluorosulfone solvents include one or more of methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, propyl trifluoromethyl sulfone, methyl trifluoroethyl sulfone, methyl trifluoropropyl sulfone, 1,1,2,2-tetrafluoropropyl methyl sulfone, trifluoromethyl isopropyl sulfone and methyl hexafluoroisopropyl sulfone; phosphate esters The solvent includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, isopropyl phosphate, tris(hexafluoroisopropyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate; the borate solvent includes one or more of trimethyl borate, triethyl borate, tris(hexafluoroisopropyl) borate and tris(2,2,2-trifluoroethyl) borate; the nitrile solvent includes acetonitrile, succinonitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyano-2-butene, 1,3,6 -hexane trinitrile, ethylene glycol dipropionitrile ether and 1,2,3-tricyanoethoxy; carbonate solvents include one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate; carboxylic acid ester solvents include one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; ether solvents include one or more of 1,2-dimethoxyethane, tetraethanol dimethyl ether, γ-butyrolactone and tetrahydrofuran.
[0145] Optionally, the solvent of the positive electrode electrolyte includes one or more of bis(trifluoromethyl)carbonate, bis(trifluoroethyl)carbonate, bisfluoroethylene carbonate, 2,2-difluoroethyl acetate, ethyl difluoroacetate, diethyl sulfone, methyl ethyl sulfone, methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, triethyl phosphate, tripropyl phosphate, acetonitrile, succinonitrile and succinonitrile.
[0146] Optionally, the solvent of the negative electrode electrolyte includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, 1,2-dimethoxyethane, and tetraethanol dimethyl ether.
[0147] In some embodiments, the lithium salt of the positive electrode electrolyte is different from the lithium salt of the negative electrode electrolyte.
[0148] It should be noted that when the types of lithium salts contained in the positive electrode electrolyte are completely different from those contained in the negative electrode electrolyte, the lithium salts in the positive electrode electrolyte and the negative electrode electrolyte are considered different. For example, if the lithium salt contained in the positive electrode electrolyte is a and the lithium salt used in the negative electrode electrolyte is b, then the lithium salts in the positive electrode electrolyte and the negative electrode electrolyte are different.
[0149] If the lithium salt type in the positive electrolyte is identical to the lithium salt type in the negative electrolyte, but the mass volume concentration or molar concentration of the lithium salt is different, then the lithium salt in the positive electrolyte and the lithium salt in the negative electrolyte are different. For example, if the lithium salt in the positive electrolyte is a with a molar concentration of 1 mol / L, and the lithium salt in the negative electrolyte is a with a molar concentration of 1.5 mol / L, then the lithium salt in the positive electrolyte and the lithium salt in the negative electrolyte are different.
[0150] When both the positive and negative electrolytes utilize multiple lithium salts, and the types of lithium salts used in the positive and negative electrolytes are exactly the same, but the mass ratios or molar ratios of the different lithium salts are different, this also falls within the category of the lithium salts in the positive and negative electrolytes being different. For example, if the lithium salt in the positive electrolyte is a mixture of a and b in a molar ratio of 5:5, and the lithium salt in the negative electrolyte is a mixture of a and b in a molar ratio of 3:7, then the lithium salts in the positive and negative electrolytes are different. Furthermore, when the types of lithium salts and the molar ratios or mass ratios of the different lithium salts in the positive and negative electrolytes are exactly the same, but the total mass volume concentrations or total molar concentrations of the lithium salts are different, this also falls within the category of the lithium salts in the positive and negative electrolytes being different. For example, the lithium salt in the positive electrode electrolyte and the lithium salt in the negative electrode electrolyte are both a mixture of a and b with a molar ratio of 5:5, but the total molar concentration of the lithium salt in the positive electrode electrolyte is 1 mol / L, and the total molar concentration of the lithium salt in the negative electrode electrolyte is 1.5 mol / L, then the lithium salt in the positive electrode electrolyte is different from the lithium salt in the negative electrode electrolyte.
[0151] When the types of lithium salts in the positive and negative electrolytes are partially the same, the lithium salts in the positive and negative electrolytes are considered different. For example, if the lithium salt in the positive electrolyte is a and the lithium salt in the negative electrolyte is a mixture of a and b, then the lithium salt in the positive and negative electrolytes are different. If the lithium salt in the positive electrolyte is a mixture of a and c and the lithium salt in the negative electrolyte is a mixture of a and c, then the lithium salt in the positive and negative electrolytes are also different.
[0152] In some embodiments, the lithium salt of the positive electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalatoborate).
[0153] In some embodiments, the lithium salt of the positive electrode electrolyte may further include one or more of lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the lithium salt in the positive electrode electrolyte is typically 0.5-5 mol / L.
[0154] In some embodiments, the lithium salt of the negative electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalatoborate).
[0155] In some embodiments, the lithium salt of the negative electrode electrolyte may further include one or more of lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the lithium salt in the negative electrode electrolyte is typically 0.5-5 mol / L.
[0156] In some embodiments, the cathode electrolyte may optionally include additives. For example, the additives may include cathode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, or additives that improve battery high or low temperature performance.
[0157] In some embodiments, the negative electrode electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, or additives that improve battery high or low temperature performance.
[0158] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The positive and negative electrolytes conduct ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0159] Positive electrode
[0160] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0161] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.
[0162] In some embodiments, the positive electrode active material includes one or more of lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and compounds obtained by adding other transition metal elements or non-transition metal elements to the above lithium-containing compounds.
[0163] As an example, lithium nickel cobalt manganese oxide may include but is not limited to LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ) and LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 )
[0164] Lithium cobalt oxides may include but are not limited to LiCoO2; lithium nickel oxides may include but are not limited to LiNiO2; lithium manganese oxides may include but are not limited to one or more of LiMnO2 and LiMn2O4; lithium nickel cobalt aluminum oxides may include but are not limited to LiNi 0.85 Co 0.15 Al 0.05 O2.
[0165] In some embodiments, the positive electrode active material may also include other positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may also include at least one of the following materials: a lithium-containing phosphate with an olivine structure. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, and a composite material of lithium manganese iron phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode active material layer is 80-100 weight %, based on the total weight of the positive electrode active material layer.
[0166] In some embodiments, at least a portion of the outer surface of the positive electrode active material has a coating layer, which can improve the stability of the positive electrode active material.
[0167] It should be noted that the coating layer may be provided on only a portion of the outer surface of the positive electrode active material, or on the entire outer surface of the positive electrode active material. For a positive electrode active material having a coating layer, the coating layer may be provided on a portion of the outer surface of the positive electrode active material, or on the entire outer surface of the positive electrode active material.
[0168] In some embodiments, the material forming the coating layer includes one or more of a carbon material, an oxide, a phosphide, a fluoride, and a polymer; optionally, the oxide includes one or more of Al2O3, SiO2, TiO2, and MgO. Alternatively, the phosphide includes one or more of NiP, Li3PO4, and FePO4. Alternatively, the fluoride includes one or more of AlF3, SrF2, and Al(OH)3.
[0169] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. The polymer material substrate includes but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0170] In some embodiments, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode active material layer is 0-20 weight%, based on the total weight of the positive electrode active material layer.
[0171] In some embodiments, the positive electrode active material layer may further optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode active material layer is 0-20% by weight, based on the total weight of the positive electrode active material layer.
[0172] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80 wt %, and the viscosity at room temperature is adjusted to 5000-25000 mPa·s, the positive electrode slurry is coated on both sides of the positive electrode current collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder is coated on one side with a unit area density of 150-450 mg / m 2 The compaction density of the positive electrode is 2-4.3g / cm 3 , optional 2.5-4.3g / cm 3 The calculation formula of the compacted density is
[0173] Compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0174] Negative electrode
[0175] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0176] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is provided on either or both of the two facing surfaces of the negative electrode current collector.
[0177] In some embodiments, the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, lithium metal, a lithium-carbon composite material, and lithium titanate; optionally, the carbon-based material includes one or more of graphite, soft carbon, hard carbon, mesophase carbon microbeads, carbon fibers, and carbon nanotubes; optionally, the silicon-based material includes one or more of elemental silicon, silicon oxides, and silicon-carbon composites.
[0178] In some embodiments, the negative electrode active material may also include other negative electrode active materials for batteries that are well known in the art. As an example, the negative electrode active material may also include at least one of the following materials: silicon-based materials, tin-based materials, etc. The silicon-based material may also be selected from at least one of silicon-nitrogen complexes and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode active material layer is 70-100 weight %, based on the total weight of the negative electrode active material layer.
[0179] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver and silver alloys, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0180] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode active material layer is 0-30% by weight, based on the total weight of the negative electrode active material layer.
[0181] In some embodiments, the negative electrode active material layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode active material layer is 0-20% by weight, based on the total weight of the negative electrode active material layer.
[0182] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). The weight ratio of the other additives in the negative electrode active material layer is 0-15% by weight, based on the total weight of the negative electrode active material layer.
[0183] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the negative electrode slurry has a solid content of 30-70 wt% and a viscosity at room temperature adjusted to 2000-10000 mPa·s; the obtained negative electrode slurry is coated on both sides of the negative electrode current collector, and after a drying process, cold pressing, such as with a roller, is performed to obtain the negative electrode sheet. The negative electrode powder is coated on one side with a unit area density of 75-220 mg / m 2 , the compaction density of the negative electrode is 1.2-2.0g / m 3 .
[0184] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0185] When preparing electrode assemblies using a lamination process, the positive electrode sheet and the negative electrode sheet can be placed close to the separator, and then the three can be placed in an aluminum-plastic bag with the same length and width as the separator. The other three sides except the opening of the aluminum-plastic bag can be heat-sealed together with the separator. The separator and the aluminum-plastic bag form dense positive and negative electrode chambers. The positive electrode electrolyte and the negative electrode electrolyte are then injected into the positive electrode chamber and the negative electrode chamber respectively from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell.
[0186] When preparing the electrode assembly by the winding process, the positive electrode sheet, the negative electrode sheet and the separator can be wound and then placed in an aluminum-plastic bag. The lower end of the aluminum-plastic bag is heat-sealed together with the separator. The separator and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber. The positive electrode electrolyte and the negative electrode electrolyte are then injected into the positive electrode chamber and the negative electrode chamber respectively from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell.
[0187] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the battery cell.
[0188] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0189] In some embodiments, the secondary battery is a lithium-ion battery.
[0190] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG12 shows a secondary battery 1 having a square structure as an example.
[0191] In some embodiments, referring to FIG13 , the outer packaging may include a housing 11 and a cover 13 . The housing 11 may include a bottom plate and side plates connected to the bottom plate, which together form a receiving cavity. The housing 11 may have an opening communicating with the receiving cavity, and the cover 13 may be positioned over the opening to seal the receiving cavity.
[0192] The positive electrode sheet, negative electrode sheet, and separator can be wound or laminated to form an electrode assembly 12. The electrode assembly 12 is enclosed in the housing. The positive electrode electrolyte is infiltrated between the positive electrode sheet and the separator, while the negative electrode electrolyte is infiltrated between the negative electrode sheet and the separator. The secondary battery 1 can contain one or more electrode assemblies 12, which can be adjusted based on demand.
[0193] In some embodiments, secondary batteries can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0194] In a battery module, multiple secondary batteries can be arranged in sequence along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, the multiple secondary batteries can be fixed by fasteners.
[0195] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of secondary batteries are accommodated in the accommodation space.
[0196] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0197] A battery pack may include a battery box and multiple battery modules disposed within the box. The battery box comprises an upper case and a lower case. The upper case can be placed over the lower case to form an enclosed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.
[0198] Electrical devices
[0199] The present application also provides an electrical device comprising at least one of the aforementioned secondary battery, battery module, or battery pack. The secondary battery, battery module, or battery pack can be used as a power source for the device or as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship, a satellite, an energy storage system, etc.; wherein the mobile device may include, but is not limited to, at least one of a mobile phone and a laptop computer; and the electric vehicle may include, but is not limited to, at least one of a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.
[0200] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0201] Figure 14 shows an example of an electric device 2. The electric device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.
[0202] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0203] The beneficial effects of the present application are further illustrated below with reference to the examples.
[0204] Example
[0205] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application. The materials used in the embodiments and comparative examples of the present application can all be obtained commercially.
[0206] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.
[0207] 1. Preparation of COF Materials
[0208] 1. TC-1 synthesis
[0209] To a reactor, 0.1 g of 1,3,5-benzenetricarboxaldehyde and p-phenylenediamine in a molar ratio of approximately 1:1 was added, followed by 3 g of 1,4-dioxane, which was fully dissolved. Under nitrogen, 0.3 g of 6 mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 96 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-1. The structural diagram of TC-1 is shown in Figure 1.
[0210] The X-ray diffraction spectrum of TC-1 was measured using a Science Ultima IV X-ray powder diffractometer. The test conditions were: Cu Kα radiation, a 2θ range of 2°-40°, a current of 40 mA, and a voltage of 30 kV. The TC-1 sample was thoroughly ground into a uniform, fine powder in an agate mortar. The powder was spread evenly into the groove of the XRD test stage and scraped flat with a glass slide until the groove filled with powder was flush with the top edge of the groove. The diffraction angle was scanned from 1° to 45°. The results are shown in Figure 9. As shown in Figure 9, the diffraction angle shows a peak at ~4.8°, indicating that the monomers are organized in an orderly manner, forming a long-range ordered structure, indicating that well-crystalline COF materials can be prepared under these conditions.
[0211] The model used is Bruker ALPHA, with a wavelength range of 400cm -1 ~4000cm -1 The infrared spectrum of TC-1 was measured by infrared spectrometer. The results are shown in Figure 10. As shown in Figure 10, at 1680 cm -1 The peak of -CHO was detected at 1613 cm -1 The -C=N- peak was detected, which further confirmed the structure of TC-1.
[0212] The prepared COF material was tested for N adsorption using a Quantachrome (ASiQMVH002 5) gas adsorption instrument at standard atmospheric pressure (101 kPa). The gas used was 99.999% pure. The test procedure involved adding 100 mg of TC-1 to a quartz sample tube and degassing it under vacuum at 120°C for 6 hours on the pretreatment station of a rapid surface area analyzer. Gas adsorption experiments were performed on the COF material using the gas adsorption instrument. Based on the resulting nitrogen adsorption curves, the pore size distribution (PSD) was calculated using nonlocal density functional theory (NLDFT). The results are shown in Figure 11. Figure 11 shows that the pore size distribution of TC-1 is primarily concentrated at 1.8 nm, indicating an internal pore size of 1.8 nm.
[0213] 2. TC-2 synthesis
[0214] To a reactor, 0.1 g of hydrazine hydrate and trialdehyde phloroglucinol in a molar ratio of approximately 1:1 was added, followed by 3 g of a 1:1 mixture of tetrahydrofuran and ethanol, allowing them to fully dissolve. Under nitrogen, 0.3 g of a 6 mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and allowed to react at 120°C for 120 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-2. The structural diagram of TC-2 is shown in Figure 2.
[0215] Using the same test method as TC-1, the pore diameter of the internal pores of TC-2 was measured to be 0.97 nm.
[0216] 3. TC-3 synthesis
[0217] To a reactor, 0.1 g of hexa(4-formylphenyl)benzene and p-phenylenediamine in a molar ratio of approximately 1:1 was added, followed by 3 g of 1,4-dioxane and ultrasonication for 5 minutes. Under nitrogen, 0.3 g of a 6 mol / L acetic acid solution was slowly added, and the mixture was transferred to an oven at 120°C and allowed to react for 48 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor with acetone for 20 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-3. The structural diagram of TC-3 is shown in Figure 3.
[0218] Using the same test method as TC-1, the pore diameter of the internal pores of TC-3 was measured to be 0.67 nm.
[0219] 4. TC-4 synthesis
[0220] To a reactor, 0.1 g of 1,3,5-triformaldehyde-2,4,6-methoxybenzene and p-1,3,5-triamino-2,4,6-methoxybenzene in a molar ratio of approximately 1:1 were added, followed by 3 g of 1,4-dioxane and 3 g of the template, mesitylene, and allowed to fully dissolve. Under nitrogen, 0.3 g of 6 mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 72 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-4. The structural diagram of TC-4 is shown in Figure 4.
[0221] Using the same test method as TC-1, the pore diameter of the internal pores of TC-4 was measured to be 0.3 nm.
[0222] 5. TC-5 synthesis
[0223] 0.1g of benzidine and trialdehyde phloroglucinol in a molar ratio of approximately 1:1 was added to a reactor, followed by 3g of a 1:1 mixture of tetrahydrofuran and ethanol, and allowed to dissolve thoroughly. Under nitrogen, 0.3g of a 6 mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and allowed to react at 120°C for 120 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-5. The structural diagram of TC-5 is shown in Figure 5.
[0224] Using the same test method as TC-1, the pore diameter of the internal pores of TC-5 was measured to be 2 nm.
[0225] 6. TC-6 synthesis
[0226] 0.1 g of 1,4-methylenediboronic acid-2,5-dimethylbenzene was added to a reactor, followed by 3 g of a 4:1 mixture of acetonitrile and 1,4-dioxane. After sonication, the mixture was thoroughly dissolved. The reactor was sealed with nitrogen and transferred to an oven at 90°C for 72 hours. The reaction mixture was filtered, and the residue was purified using a Soxhlet extractor with tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named TC-6. The structural diagram of TC-6 is shown in Figure 6.
[0227] Using the same test method as TC-1, the pore diameter of the internal pores of TC-6 was measured to be 0.8 nm.
[0228] 7. TC-7 synthesis
[0229] To a reactor, 0.1 g of 1,3,5-tris[4-amino(phenyl-4-yl)]benzene and 4,4′-(6-phenylphenanthrene-3,8-diacyl)benzaldehyde (at a molar ratio of approximately 1:1) were added, followed by 3 g of 1,4-dioxane, which was fully dissolved. Under nitrogen, 3 g of mesitylene (templating agent) was added. After 5 minutes of simmering, 0.3 g mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 72 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor with methanol for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-7. The structural diagram of TC-7 is shown in Figure 7.
[0230] Using the same test method as TC-1, the pore diameter of the internal pores of TC-7 was measured to be 4.8 nm.
[0231] 8. TC-8 synthesis
[0232] To a reactor, 0.1 g of 1,3,5-tris[4-amino(1,1-biphenyl-4-yl)]benzene and 4,4′-(6-phenylphenanthrene-3,8-diacyl)benzaldehyde (at a molar ratio of approximately 1:1) were added, followed by 3 g of 1,4-dioxane, which was fully dissolved. Under nitrogen, 3 g of mesitylene (templating agent) was added. After 5 minutes of simmering, 0.3 g mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 72 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor with methanol for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, designated TC-8. The structural diagram of TC-8 is shown in Figure 8.
[0233] Using the same test method as TC-1, the pore diameter of the internal pores of TC-8 was measured to be 5.8 nm.
[0234] It should be noted that since COF materials synthesized using the same monomers have the same internal pore diameter, the resulting COF materials can further adjust the volume average particle size (Dv50) of the resulting COF materials by controlling the reaction conditions during the COF material preparation process. For ease of description, COF materials synthesized using the same monomers and having the same internal pore diameter will be uniformly named in this application.
[0235] 2. Preparation of isolation membrane
[0236] 1. Example 1
[0237] The COF material TC-1 was mixed with polyvinylidene fluoride (as a binder), and then N-methylpyrrolidone was added, stirred, and dispersed to prepare a coating slurry. The coating slurry was mixed with 105 mg / 1540.25 cm 2 A coating weight of 100 μg / cm2 was applied simultaneously to both sides of a PE separator (serving as the separator substrate). After coating, the separator was dried, cold-pressed, and slit to produce the separator. The volume average particle size (Dv50) of TC-1 was 100 nm, and the total coating thickness was 8 μm. The mass ratio of TC-1 to binder was 96:4, resulting in a 96% weight ratio of TC-1 in the coating.
[0238] 2. Example 2-14
[0239] The preparation method of the isolation membrane in Examples 2-14 is basically similar to the preparation method of the isolation membrane in Example 1. The main difference lies in: at least one of the type of COF material, the pore size of the internal pores of the COF material, the volume average particle size Dv50 of the COF material, the mass proportion of the COF material in the coating, and the thickness of the coating. See Table 1 for details.
[0240] It should be noted that in Examples 2-3, the coating slurry was applied on one side of the PE separator, and in Examples 4-16, the coating slurry was applied on both sides of the PE separator, with the thickness on both sides being the same.
[0241] 3. Comparative Examples 1-6
[0242] The preparation methods of the isolation membranes in Comparative Examples 1-6 are basically similar to the preparation method of the isolation membrane in Example 1, with the main differences being: at least one of the type of COF material, the pore size of the internal pores of the COF material, the volume average particle size Dv50 of the COF material, the mass proportion of the COF material in the coating, and the thickness of the coating. See Table 1 for details.
[0243] It should be noted that in Comparative Examples 1-2 and Comparative Examples 4-6, the coating slurry was applied on both sides of the PE separator, and the thickness on both sides was the same. In Comparative Example 3, the coating slurry was applied on one side of the PE separator.
[0244] The preparation parameters of the isolation membranes in the above embodiments and comparative examples are shown in Table 1.
[0245] Table 1
[0246] Wherein, D represents the pore size of the internal pores of the COF material; d represents the volume average particle size Dv50 of the COF material; L represents the thickness of the coating; n represents the mass ratio of the COF material in the coating; F represents Calculation results, where the unit of L is converted to nanometers during calculation.
[0247] It should be noted that the volume average particle size (Dv50) of the COF material mentioned above was measured using a Microtrac MRB S3500 series laser particle size analyzer. The specific process is: 2g of COF material was added to 20mL of deionized water, and ultrasonicated for 5 minutes to ensure that the sample was completely dispersed to obtain a dispersion. The dispersion was then placed in a sample tank and tested to obtain the volume average particle size (Dv50) of the COF material.
[0248] 3. Preparation of Secondary Batteries
[0249] Example 17
[0250] 1. Preparation of positive electrode sheet
[0251] Lithium cobalt oxide (as the positive electrode active material), conductive carbon black (as the conductive agent), and polyvinylidene fluoride (as the binder) are mixed in a mass ratio of 97:1:2. N-methylpyrrolidone is then added and stirred to form a positive electrode slurry. The positive electrode slurry is then coated on aluminum foil. After both sides are coated, it is dried, cold pressed, and slit to produce the positive electrode sheets.
[0252] 2. Preparation of negative electrode sheet
[0253] Artificial graphite (as the negative electrode active material), conductive carbon black (as the conductive agent), styrene-butadiene rubber (as the binder), and sodium carboxymethyl cellulose (as the thickener) are mixed in a mass ratio of 95:1:2:2. Deionized water is then added and stirred to form a negative electrode slurry. The negative electrode slurry is then coated on copper and aluminum foil. After both sides are coated, the negative electrode sheet is dried, cold pressed, and slit.
[0254] 3. Preparation of Electrolyte
[0255] Preparation of positive electrode electrolyte: In a glove box filled with argon (water <10ppm, oxygen <10ppm), ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) were uniformly mixed in a mass ratio of EC:PC:EMC=5:10:85, 3wt% of succinonitrile (SN) and 2wt% of fluoroethylene carbonate (FEC) were added to the mixture and mixed thoroughly. Finally, lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution until the molar concentration of LiPF6 was 1.15mol / L to prepare the positive electrode electrolyte.
[0256] Preparation of negative electrode electrolyte: In an argon-filled glove box (water <10ppm, oxygen <10ppm), ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) were uniformly mixed in a mass ratio of EC:PC:EMC=5:10:85, 5wt% of fluoroethylene carbonate (FEC) was added to the mixture and mixed thoroughly, and finally lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution until the molar concentration of LiPF6 was 1.15mol / L to prepare the negative electrode electrolyte.
[0257] 4. The isolation film prepared in Example 1 was used.
[0258] 5. Preparation of battery cells
[0259] The prepared positive electrode sheet and negative electrode sheet are placed close to the separator, and the three are placed in an aluminum-plastic bag with the same length and width as the separator. The other three sides of the aluminum-plastic bag except the one before the opening are heat-sealed together with the separator. The separator and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber. The above-mentioned positive electrode electrolyte and negative electrode electrolyte are respectively injected into the positive electrode chamber and the negative electrode chamber, and the battery cell is obtained after sealing.
[0260] Examples 18-32
[0261] The preparation methods of the secondary batteries in Examples 18-32 are basically similar to the preparation method of the secondary battery in Example 17, with the main difference being that different isolation membranes are used. See Table 2 for details.
[0262] Examples 33-34
[0263] The preparation method of the secondary battery in Examples 33-34 is basically similar to the preparation method of the secondary battery in Example 17, with the main difference being that the positive electrode electrolyte and / or the negative electrode electrolyte are different. See Table 2 for details.
[0264] Comparative Examples 7-12
[0265] The preparation methods of the secondary batteries in Comparative Examples 7-12 are basically similar to the preparation method of the secondary battery in Example 17, with the main difference being that different isolation membranes are used. See Table 2 for details.
[0266] Comparative Example 13
[0267] The preparation method of the secondary battery in Comparative Example 13 is basically similar to the preparation method of the secondary battery in Example 17, with the main difference being that the positive electrode electrolyte and / or the negative electrode electrolyte are different. See Table 2 for details.
[0268] 4. Secondary Battery Performance Test
[0269] 1. Cyclic performance test
[0270] 1.1 The battery cells prepared in the above embodiments and comparative examples were respectively allowed to stand at 25°C for 30 minutes; 1.2 Discharge at a constant current of 0.33C to 2.5V; 1.3 Allow to stand at 25°C for 5 minutes; 1.4 Charge at a constant current of 0.33C to 4.48V, and charge at a constant voltage with a cut-off current of 0.05C; 1.5 Allow to stand at 25°C for 5 minutes; 1.6 Discharge at a constant current of 0.33C to 2.5V; 1.7 Allow to stand at 25°C for 5 minutes; 1.8 Cycle steps 1.1-1.7 1000 times, and measure the capacity retention rate of the battery cells.
[0271] 2. Storage performance test
[0272] 2.1 The cells prepared in the above embodiments and comparative examples were allowed to stand at 25°C for 30 minutes; 2.2 Discharged at a constant current of 0.33C to 2.5V; 2.3 Allowed to stand at 25°C for 30 minutes; 2.4 Charged at a constant current of 0.33C to 4.48V, constant voltage charging, and a cut-off current of 0.05C; 2.5 Allowed to stand at 25°C for 5 minutes; 2.6 Discharged at a constant current of 0.33C to 2.5V, and the capacity at this time was recorded as the initial reversible capacity; 2.7 Allowed to stand at 25°C for 5 minutes; 2.8 Charged at a constant current of 0.33C to 4.48V, constant voltage charging, and a cut-off current of 0.05C; 2.9 Let stand at 25°C for 5 minutes; 3.0 Transfer to a 60°C constant temperature box and let stand for 60 minutes to allow the battery cell to heat up to 60°C; 3.1 After storing for 7 days, remove from the oven and repeat steps 2.1-2.6 to obtain the reversible capacity of the battery cell after 7 days of storage; 3.2 Repeat steps 2.7-3.1 until the battery cell is stored for 140 days and then measure the battery cell capacity retention rate.
[0273] 3. Storage gas production test
[0274] 3.1 The battery cells prepared in the above embodiments and comparative examples were respectively allowed to stand at 25°C for 30 minutes; 3.2 Discharged at a constant current of 0.33C to 2.5V; 3.3 Allowed to stand at 25°C for 30 minutes; 3.4 Charged at a constant current of 0.33C to 4.48V, constant voltage charging, and a cut-off current of 0.05C; 3.5 Allowed to stand at 25°C for 5 minutes; 3.6 Determined the initial volume of the battery cell by the silicone oil drainage method; 3.7 Transferred to a 60°C constant temperature box and allowed to stand for 60 minutes to raise the temperature of the battery cell to 60°C; 3.8 After storage for 5 days, removed from the oven, and steps 3.4-3.7 were repeated to obtain the volume change of the battery cell after 5 days; 3.9 Repeated steps 2.7-3.1 until the battery cell was stored for 100 days, and the increase in the volume of the battery cell was measured, which was recorded as the gas production of the battery cell for 100 days.
[0275] 4. Rate performance test
[0276] 4.1 The battery cells prepared in the above embodiments and comparative examples were respectively allowed to stand at 25°C for 30 minutes; 4.2 Discharge at a constant current of 0.33C to 2.5V; 4.3 Allow to stand at 25°C for 30 minutes; 4.4 Discharge at a constant current of 0.05C to 2.5V; 4.5 Allow to stand at 25°C for 30 minutes; 4.6 Charge at a constant current of 2C to 4.48V. Record the charging time of this step. The longer the time, the better the charging rate.
[0277] The performance test results of the above embodiments and comparative examples are shown in Table 2.
[0278] Table 2
[0279] Wherein, EC represents ethylene carbonate, PC represents propylene carbonate, EMC represents ethyl methyl carbonate, SN represents succinonitrile, FEC represents fluoroethylene carbonate, FEP represents 2,2-difluoroethyl acetate, and LiPF6 represents lithium hexafluorophosphate.
[0280] It can be seen from the results of Examples 17-32 in Table 2 that by adjusting the pore size of the internal pores of the COF material, the volume average particle size Dv50 and the thickness of the coating to form a coating on the surface of the diaphragm substrate, the isolation membrane finally obtained can effectively inhibit the interaction between the positive and negative electrodes, and improve the long cycle performance and high temperature storage performance of the secondary battery.
[0281] The difference between Example 17, Examples 29-32 and Comparative Example 7 is that the pore diameters of the internal pores of the COF material in the isolation membrane are different; the pore diameter of the internal pores of the COF material in Comparative Example 7 is the largest, and the pore diameter of the internal pores of the COF material in Example 29 is the smallest; compared with Example 17 and Examples 29-32, the capacity retention rate of the secondary battery in Comparative Example 7 after 1000 cycles and the capacity retention rate after 140 days of storage are significantly reduced, the volume change rate after 100 days of storage is significantly increased, and the 2C charging time is significantly increased, indicating that when the pore diameter of the internal pores of the COF material is too large, the long cycle performance, high temperature storage performance and rate performance of the secondary battery are all reduced; it is speculated that the reason may be that when the pore diameter of the internal pores of the COF material is higher than 5nm, other substances in the electrolyte except lithium ions can also pass through the diaphragm, and the effect of the positive and negative electrode interaction is deteriorated.
[0282] The main difference between Examples 24-28 and Comparative Examples 9-10 lies in the volume average particle size Dv50 of the COF material in the separator. Comparative Example 10 has the largest volume average particle size Dv50, while Comparative Example 9 has the smallest volume average particle size Dv50. Compared with Examples 24-28, the capacity retention rate of the secondary battery in Example 9 after 1000 cycles and after 140 days of storage at 60°C decreases, and the volume change rate after 100 days of storage increases significantly. The capacity retention rate of the secondary battery in Example 10 decreases significantly after 1000 cycles. These results indicate that a volume average particle size Dv50 of the COF material in the separator within the range of 5nm-200nm is beneficial for suppressing the interaction between the positive and negative electrodes.
[0283] The difference between Comparative Examples 6 and 8 and Example 17 is that the ratio of the coating thickness to the volume average particle size Dv50 of the COF material in Comparative Examples 6 and 8 is less than 50; compared with Example 17, the capacity retention rate of the secondary batteries after 1000 cycles and the capacity retention rate after storage at 60°C for 140 days in Comparative Examples 6 and 8 are significantly reduced, and the volume change rate after storage for 100 days is significantly increased; technicians analyzed the reason and found that it may be because when the ratio of the coating thickness to the volume average particle size Dv50 of the COF material is lower than 50, the lithium ions and other substances in the electrolyte tend to pass through the isolation membrane through the gaps between the COF material particles, and the isolation membrane cannot effectively inhibit the exchange between the positive and negative electrodes, thereby affecting the long cycle performance and high temperature storage performance of the secondary battery.
[0284] The difference between Comparative Example 11 and Example 17 is that the positive and negative electrolytes in Comparative Example 11 are the same. Compared with Example 17, the capacity retention of the secondary battery in Comparative Example 11 decreased significantly after 1000 cycles, the capacity retention decreased after 140 days of storage at 60°C, and the volume change increased after 100 days of storage. This is presumably due to the presence of SN in the negative electrolyte, which damages the negative electrode, resulting in poor long-cycle performance of the secondary battery. However, the separator can block the interaction between the positive and negative electrodes, resulting in better storage performance of the secondary battery.
[0285] This shows that when the corresponding positive electrode electrolyte and negative electrode electrolyte are set according to the characteristics of the positive electrode and negative electrode respectively, the advantages of different electrolytes can be magnified, and the long cycle performance and high temperature storage performance of the secondary battery can be further improved.
[0286] The difference between Example 18 and Example 28 lies in the thickness of the coating in the separator, while the difference between Example 19 and Example 26 lies primarily in the thickness of the coating in the separator. The coating thickness in Example 28 is greater than that in Example 18, and the coating thickness in Example 26 is greater than that in Example 19. Compared with Example 18, the 2C charging time of the secondary battery in Example 28 is extended; compared with Example 19, the 2C charging time of the secondary battery in Example 26 is extended. This indicates that when the volume average particle size Dv50 of the COF material is smaller, the coating becomes denser and more suitable for thin coating. The separator has excellent ion conductivity, thereby improving the rate performance of the secondary battery.
[0287] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present application, and such modifications or substitutions should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. A separation film comprising: Diaphragm substrate; a coating layer, located on at least one side of the membrane substrate, the coating layer comprising a covalent organic framework material; Among them, the pore size of the internal pores of the covalent organic framework material is recorded as D, the volume average particle size Dv50 of the covalent organic framework material is recorded as d, and the total thickness of the coating is recorded as L. The pore size of the internal pores of the covalent organic framework material satisfies: 0.04nm≤D≤5nm, the volume average particle size Dv50 of the covalent organic framework material and the total thickness of the coating satisfy: 50≤L / d≤2000.
2. The isolation membrane according to claim 1, wherein the pore size of the internal pores of the covalent organic framework material, the volume average particle size Dv50 of the covalent organic framework material and the total thickness of the coating satisfy: 3 . The isolation membrane according to claim 1 , wherein the pore size of the internal pores of the covalent organic framework material satisfies: 0.04 nm≤D≤2 nm. 4 . The isolation membrane according to claim 1 , wherein the volume average particle size Dv50 of the covalent organic framework material satisfies: 5 nm ≤ d ≤ 200 nm; optionally 20 nm ≤ d ≤ 100 nm. 5 . The isolation film according to claim 1 , wherein the total thickness of the coating satisfies: 2 μm≤L≤30 μm; optionally 5 μm≤L≤15 μm.
6. The isolation membrane according to any one of claims 1 to 5, wherein the covalent organic framework material comprises one or more of homopolymers and copolymers of M2 monomers, M3 monomers, M4 monomers and M6 monomers; in, The M2 monomer includes 2 functional groups that can participate in polymerization reaction, the M3 monomer includes 3 functional groups that can participate in polymerization reaction, the M4 monomer includes 4 functional groups that can participate in polymerization reaction, and the M6 monomer includes 6 functional groups that can participate in polymerization reaction.
7. The isolation membrane according to claim 6, wherein the functional group capable of participating in polymerization reaction comprises one or more of a carboxyl group, a hydroxyl group, an aldehyde group, an amino group, a borate group, a hydrazine group, a cyano group, a carbonyl group and an anhydride group. 8 . The isolation membrane according to claim 6 , wherein the covalent organic framework material comprises one or more of a copolymer of the M2 monomer and the M3 monomer and a copolymer of the M2 monomer and the M6 monomer.
9. The isolation film according to any one of claims 1 to 8, wherein the connecting groups between the monomers polymerized to form the covalent organic framework material include One or more of a boryloxy group, -C=N-, a triazine group, -C=NN=C-, -C=C-, -CO-NH-, -C=N-NH-CO- and an imidazole group. 10 . The isolation membrane according to claim 1 , wherein the mass proportion of the covalent organic framework material in the coating is 80% to 96%.
11. The isolation film according to any one of claims 1 to 10, wherein the coating further comprises a binder; Optionally, the binder accounts for 4% to 20% by mass in the coating.
12. The release film of claim 11, wherein the binder comprises one or more of homopolymers or copolymers of vinylidene fluoride, ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, acrylic acid, and acrylonitrile. 13 . The separator according to claim 1 , wherein the separator substrate comprises one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. 14 . A secondary battery comprising the separator according to claim 1 .
15. The secondary battery according to claim 14, wherein the secondary battery further comprises: Positive electrode sheet, negative electrode sheet, positive electrode electrolyte and negative electrode electrolyte; The isolation membrane is located between the positive electrode plate and the negative electrode plate, the positive electrode electrolyte is located between the positive electrode plate and the isolation membrane, and the negative electrode electrolyte is located between the negative electrode plate and the isolation membrane; one or more of the solvents, lithium salts and additives contained in the positive electrode electrolyte and the negative electrode electrolyte are different.
16. The secondary battery according to claim 15, wherein the solvent of the positive electrode electrolyte is different from the solvent of the negative electrode electrolyte; Optionally, the solvent of the positive electrode electrolyte includes one or more of carbonate solvents, fluorocarbonate solvents, fluorocarboxylate solvents, sulfone solvents, fluorosulfone solvents, phosphate solvents, borate solvents and nitrile solvents; Optionally, the solvent of the negative electrode electrolyte includes one or more of carbonate solvents, carboxylate solvents, ether solvents, fluorinated carboxylate solvents and fluorinated carbonate solvents.
17. The secondary battery according to claim 16, wherein the fluorocarbonate solvent comprises one or more of methyl trifluoroethyl carbonate, bis(trifluoromethyl) carbonate, bis(trifluoroethyl) carbonate, 4-trifluoromethyl ethylene carbonate, bisfluoroethylene carbonate, trifluoromethyl trifluoroethyl carbonate, trifluoropropyl carbonate and 2,2-difluoroethyl methyl carbonate; The fluorocarboxylic acid ester solvents include 3,3,3-trifluoroethyl trifluoroacetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate and acetic acid. One or more of 2,2,2-trifluoroethyl ester; The sulfone solvent includes one or more of sulfolane, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, diethyl sulfoxide and methyl ethyl sulfoxide; The fluorinated sulfone solvent includes one or more of methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, propyl trifluoromethyl sulfone, methyl trifluoroethyl sulfone, methyl trifluoropropyl sulfone, 1,1,2,2-tetrafluoropropyl methyl sulfone, trifluoromethyl isopropyl sulfone and methyl hexafluoroisopropyl sulfone; The phosphate ester solvent includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, isopropyl phosphate, tris(hexafluoroisopropyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate; The borate ester solvent includes one or more of trimethyl borate, triethyl borate, tri(hexafluoroisopropyl) borate and tri(2,2,2-trifluoroethyl) borate; The nitrile solvent includes one or more of acetonitrile, succinonitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyano-2-butene, 1,3,6-hexanetrinitrile, ethylene glycol dipropionitrile ether and 1,2,3-tricyanoethoxy; The carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate; The carboxylate solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; The ether solvent includes one or more of 1,2-dimethoxyethane, tetraethanol dimethyl ether, γ-butyrolactone and tetrahydrofuran.
18. The secondary battery according to any one of claims 15 to 17, wherein the lithium salt of the positive electrode electrolyte is different from the lithium salt of the negative electrode electrolyte; Optionally, the lithium salt of the positive electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate); Optionally, the lithium salt of the negative electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate).
19. The secondary battery according to any one of claims 15 to 18, wherein the positive electrode sheet comprises: Positive electrode current collector; A positive electrode active material layer, located on at least one side of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material; Optionally, the positive electrode active material includes lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and one or more compounds obtained by adding other transition metal elements or non-transition metal elements to the above lithium-containing compounds.
20. The secondary battery according to any one of claims 15 to 19, wherein the negative electrode sheet comprises: Anode current collector; A negative electrode active material layer, located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material; Optionally, the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, lithium metal, a lithium-carbon composite material, and lithium titanate; Further optionally, the carbon-based material includes one or more of graphite, soft carbon, hard carbon, mesocarbon microbeads, carbon fibers and carbon nanotubes; Further optionally, the silicon-based material includes one or more of elemental silicon, silicon-oxygen compounds and silicon-carbon composites.
21. An electrical device, characterized in that: Comprising the secondary battery as claimed in any one of claims 14 to 20.